2006
DOI: 10.1159/000093375
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Olfactory Preferences II. Olfactory Receptor Neuron Responses from <i>Heliothis subflexa</i> × <i>Heliothis virescens</i> Hybrid Male Moths

Abstract: Single-cell electrophysiological recordings were obtained from olfactory receptor neurons (ORNs) in sensilla trichodea on male antennae of hybrids formed mainly by crossing female Heliothis subflexa with male Heliothis virescens (‘SV hybrids’). We recorded from the A-, B-, and C-type sensilla trichodea, with the latter two types housing ORNs exhibiting response profiles to different pheromone components that we had previously found to be characteristic for each species. For both the B- and the C-type SV hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 87 publications
(68 reference statements)
2
28
0
Order By: Relevance
“…In fact, two individuals possessed both parent-and hybrid-like cells in the same sensillum. The relationship between transcription factors and OR genes has been suggested as a pathway for the unique responses found in Heliothine hybrids (Baker et al, 2006). However, unlike the Heliothine study where the hybrid ORNs displayed a stereotypical, though unique, set of responses from the parents, the Rhagoletis hybrid ORN response profiles were much more diverse, and almost random in appearance.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In fact, two individuals possessed both parent-and hybrid-like cells in the same sensillum. The relationship between transcription factors and OR genes has been suggested as a pathway for the unique responses found in Heliothine hybrids (Baker et al, 2006). However, unlike the Heliothine study where the hybrid ORNs displayed a stereotypical, though unique, set of responses from the parents, the Rhagoletis hybrid ORN response profiles were much more diverse, and almost random in appearance.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study of chemoreception in hybrids between two closely related moth species, Heliothis virescens and H. subflexa, found that some hybrid ORNs responded to unique combinations of pheromone components absent from either parent species (Baker et al, 2006). Combined with both flight tunnel assays (Vickers, 2006a) and antennal lobe recordings (Vickers, 2006b), Baker et al (Baker et al, 2006) postulated that the "broad yet specific tuning of certain ORN types" suggests that multiple olfactory receptors were expressed in the dendritic membranes of the olfactory neurons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations